Microstructures, mechanical properties and oxidation behavior of vacuum annealed TiZrN thin films. (May 2015) - Tung, Hsiao-Ming; Wu, Po-Hsien; Yu, Ge-Ping; Huang, Jia-Hong
Abstract: The purpose of this study was to investigate the effects of vacuum heat treatments on microstructures, associated mechanical behavior and oxidation behavior of TiZrN films. The films with three Zr/(Zr + Ti) ratios of 0.3, 0.5 and 0.7 were prepared using a DC reactive unbalanced magnetron sputter system. The annealing temperatures ranged from 700 to 1000 °C. X-ray diffraction (XRD) and microstructural examination revealed that both the as-deposited and heat-treated films exhibited a single TiZrN phase with columnar grains at the annealing temperature below 900 °C. At 1000 °C, ZrO2 phase appeared. In a temperature range from 700 to 900 °C in vacuum for 3 h, the heat-treated films showed a 15% drop in hardness, as compared with the as-deposited films. The slight decrease in hardness suggested that the heat-treated TiZrN films with a hardness level of application interest could be attributed to solid solution strengthening. Stress state of the films was found to be compressive. Substantial decrease in the magnitude of the residual compressive stresses could be achieved via heat treatment. At 1000 °C, the volume expansion arising from the oxidation of zirconium within the film may lead to an increase in residual compressive stresses of the films. The Ti0.7 Zr0.3 N film exhibited a lowest oxidation rate in the TiZrN coatings at 1000 °C in vacuum. Highlights: Residual stress of the heat-treated TiZrN films is decreased. Solid solution strengthening keeps the films with a hardness level of application interest. The Ti0.7 Zr0.3 N film exhibited a lowest oxidation rate in the TiZrN coatings.